Preparation method of sealant for hyperbaric oxygen chamber

By using a composite matrix resin of polyurethane prepolymer and epoxy resin in the high-pressure oxygen chamber sealant, combining epoxy block copolymer and temperature-responsive microcapsules, the problem of aging and damage of sealant in a high-pressure environment is solved, and the problem of sealant is achieved. It has stable sealing performance and self-repair ability under extreme conditions, improving the durability and reliability of sealant.

CN119286453AInactive Publication Date: 2025-01-10ZHEJIANG RUNRUN ENVIRONMENTAL PROTECTION ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411636765.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-pressure oxygen chamber sealant is prone to aging, cracking or damage in high-pressure environments, and it is difficult to meet the requirements of flexibility and strength at the same time under extreme conditions. The efficiency of self-healing materials is also weak, especially in complex temperature environments. Inadequate ability.

Method used

Using a composite matrix resin structure of polyurethane prepolymer and epoxy resin, combined with epoxy block copolymer with self-healing characteristics and temperature-responsive microcapsules, a toughener is added through finely controlled cross-linking curing and ultrasonic dispersion treatment, and Nanofillers form sealants with excellent sealing properties, self-healing ability and automatic temperature adjustment.

Benefits of technology

It significantly improves the durability and sealing performance of sealant, extends service life, can maintain stable performance under high pressure and high temperature environments, adapts to different temperature conditions, has impact resistance, ultraviolet resistance and anti-aging properties, and improves the reliability of sealant sex.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of sealants, and discloses a sealant for a hyperbaric oxygen chamber and a preparation method thereof, the sealant comprises 50%-60% of matrix resin, 13%-17% of a flexibilizer, 9%-13% of a curing agent, 5%-9% of a self-healing material, and 10%-20% of other materials; wherein the self-healing material comprises 3%-5% of an epoxy block copolymer and 2%-4% of a temperature response microcapsule. The preparation method of the sealant comprises the following steps: mixing the matrix resin, heating the polyurethane prepolymer to 70-80 DEG C, adding the epoxy resin, and stirring for 30 minutes to fully mix to form the matrix resin; adding other materials, namely sequentially adding the toughening agent, the self-healing material, the filler, the auxiliary agent, the curing agent and the catalyst; cross-linking and curing: carrying out cross-linking and curing layer by layer in the mold; and degassing treatment: placing the mixture in a vacuum degassing device, and keeping vacuum for 20 minutes to remove bubbles so as to form the sealant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sealants, and in particular to a method for preparing sealants for a hyperbaric oxygen chamber. Background Art

[0002] Hyperbaric oxygen chambers are widely used in medical rehabilitation and diving, and have the effect of assisting treatment and improving physical condition. However, the hyperbaric oxygen chamber needs to withstand high internal pressure when working, and the sealing requirements of the chamber are extremely strict. Any slight leakage may bring serious safety hazards. Therefore, sealants play a vital role in the sealing structure of hyperbaric oxygen chambers.

[0003] Traditional hyperbaric oxygen chamber sealants are usually based on a single resin system and have certain sealing and pressure resistance capabilities, but they are prone to aging, cracking or damage under high-pressure environments, thereby reducing the sealing performance. In recent years, self-healing materials have been used in the sealing field to improve the service life of sealants by repairing tiny cracks. However, the self-healing efficiency of existing self-healing materials still needs to be improved, especially the response ability in complex temperature environments is relatively weak. In addition, the flexibility and strength of the sealant need to be balanced, and existing materials are difficult to meet these two requirements at the same time under extreme conditions. Therefore, it is of great significance to develop a hyperbaric oxygen chamber sealant that has high sealing, excellent self-healing properties and controllable temperature response. Summary of the invention

[0004] In view of this, the present invention proposes a use of a plant extract in the preparation of a drug for treating hepatic encephalopathy, aiming to solve the problem in current technology that the flexibility and strength of sealants need to be balanced, and existing materials are difficult to meet these two requirements at the same time under extreme conditions.

[0005] On the one hand, the sealant for a hyperbaric oxygen chamber provided by the present invention comprises: 50%-60% of a base resin, 13%-17% of a toughening agent, 9%-13% of a curing agent, 5%-9% of a self-healing material, and 10%-20% of other materials;

[0006] The self-healing material comprises 3%-5% of epoxy block copolymer and 2%-4% of temperature responsive microcapsules.

[0007] Optionally, the other materials include fillers, additives and catalysts;

[0008] The filler comprises 2-5% nano silicon dioxide, 1-3% boron carbide powder, 1-2% carbon nanotubes and 2-3% graphene-alumina composite nano powder;

[0009] The auxiliary agent includes 2.5-4% phthalic acid esters, 1-2% nano cerium oxide CeO2, and 0.5-1% ultraviolet absorber;

[0010] The catalyst comprises 0.1-0.3% of an organic tin compound and 0.1-0.2% of an organic silane coupling agent.

[0011] Optionally, the matrix resin includes 45-50% polyurethane prepolymer and 5-10% epoxy resin;

[0012] The toughening agent comprises 10-15% polyether polyol and 3-5% hydroxyl-terminated polybutadiene;

[0013] The curing agent comprises 8-11% of diphenylmethane diisocyanate and 1-2% of an amine curing agent.

[0014] Optionally, the preparation method of the epoxy block copolymer is:

[0015] Select diglycidyl ether and polyoxypropylene glycol,

[0016] Add carboxyl or amino initiator, control the temperature to 50-60°C, initiate polymerization reaction, and form epoxy block copolymer;

[0017] During the copolymerization process, a linear or branched epoxy block copolymer structure is formed by regulating the concentration of the initiator and the reaction time;

[0018] After polymerization, a small amount of thiol compounds and a modifier amine curing agent are added to react at 80° C. for 2 hours to cure to form an epoxy block copolymer with self-healing function.

[0019] Optionally, the preparation method of the temperature-responsive microcapsule is:

[0020] Dispersing the lubricant in the water phase, adding polyethylene glycol stearate, and stirring at 50°C to form an emulsion;

[0021] Select polymethyl methacrylate as the shell material of the microcapsule, add it dropwise into the emulsion, and control the pH value at 7-8;

[0022] Poly (N-isopropylacrylamide) was added to the microcapsule preparation, and the microcapsule shell material was maintained at 40-50°C for 30 minutes to undergo structural changes;

[0023] After the coating is completed, the microcapsules are heated to 60°C for curing and then dried under vacuum conditions to form temperature-responsive microcapsules.

[0024] On the other hand, the present invention also provides a method for preparing a sealant for a hyperbaric oxygen chamber, comprising the following steps:

[0025] Mixing the matrix resin: Heat the polyurethane prepolymer to 70-80°C, add the epoxy resin and stir for 30 minutes to fully mix to form the matrix resin;

[0026] Add other materials, such as toughening agent, self-healing material, filler, additive, curing agent and catalyst in sequence;

[0027] Cross-linking and curing: cross-linking and curing layer by layer in the mold;

[0028] Degassing treatment: Place the mixture in a vacuum degassing device and maintain vacuum for 20 minutes to remove bubbles and form a sealant.

[0029] Optionally, the layer-by-layer cross-linking and curing includes: pre-curing at 50-60°C for 1 hour, gradually heating up to 80°C, and then completing final curing at 90°C.

[0030] Optionally, the toughening agent is added when the base resin is cooled to 60° C., and stirring is continued for 20 minutes.

[0031] Optionally, after the filler is added, ultrasonic dispersion treatment is performed, and the ultrasonic dispersion treatment time is 20 minutes.

[0032] Optionally, the auxiliary agent is added at 70° C. and stirred for 30 minutes. After the curing agent is added, the temperature needs to be maintained at 60° C. and stirred for 30 minutes.

[0033] Compared with the prior art, the beneficial effect of the present invention is that the sealant of the present invention not only improves the sealing of the material, but also significantly enhances the durability by adopting a composite matrix resin structure of polyurethane prepolymer and epoxy resin, so that the sealant maintains excellent performance under high pressure and high temperature environment. The composite matrix can effectively resist the erosion of pressure and oxygen on the material and extend the service life of the sealant. The epoxy block copolymer and temperature-responsive microcapsules with self-healing properties are used to give the sealant self-healing ability under high pressure environment. The linear and branched structures in the epoxy block copolymer are precisely controlled so that the sealant can quickly self-heal when damaged, repair tiny cracks and surface damage, and significantly improve the long-term sealing performance of the sealant. The temperature-responsive microcapsules in the present invention can release internal lubricants under specific temperature conditions, so that the flexibility and strength of the sealant can be automatically adjusted in temperature changes. This design enables the sealant to maintain stable sealing performance under temperature fluctuations or extreme temperature conditions, thereby adapting to sealing requirements in different environments. The sealant has high flexibility and strength while ensuring sealing performance by adding toughening agents (polyether polyol and terminal hydroxyl polybutadiene) and fillers (nano silicon dioxide, boron carbide powder, etc.) to the matrix, meeting the stringent requirements of the hyperbaric oxygen chamber for sealing materials. The introduction of nanofillers and reinforcing additives improves the mechanical properties of the colloid, so that the sealant has stronger impact resistance when under pressure or vibration. By introducing ultraviolet absorbers and nano cerium oxide (CeO2), the sealant has stronger ultraviolet resistance and anti-aging properties. Even under long-term lighting conditions, the material can effectively delay the aging process and maintain a high-performance sealing effect, thereby significantly improving the application life and reliability of the sealant. The preparation method of the present invention achieves uniform distribution of each component in the sealant through fine control of the steps of staged cross-linking curing, ultrasonic dispersion treatment and degassing, thereby improving the structural stability and overall performance of the sealant. The temperature control and ultrasonic dispersion technology of the layer-by-layer curing process fully combine components such as fillers and toughening agents, further optimizing the sealing, strength and durability of the sealant. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] On the one hand, the sealant for a hyperbaric oxygen chamber provided by the present invention comprises: 50%-60% of a base resin, 13%-17% of a toughening agent, 9%-13% of a curing agent, 5%-9% of a self-healing material, and 10%-20% of other materials;

[0036] The self-healing material comprises 3%-5% of epoxy block copolymer and 2%-4% of temperature responsive microcapsules.

[0037] In this preferred embodiment, the other materials include fillers, additives and catalysts;

[0038] The filler comprises 2-5% nano silicon dioxide, 1-3% boron carbide powder, 1-2% carbon nanotubes and 2-3% graphene-alumina composite nano powder;

[0039] The auxiliary agent includes 2.5-4% phthalic acid esters, 1-2% nano cerium oxide CeO2, and 0.5-1% ultraviolet absorber;

[0040] The catalyst comprises 0.1-0.3% of an organic tin compound and 0.1-0.2% of an organic silane coupling agent.

[0041] In this preferred embodiment, the matrix resin includes 45-50% polyurethane prepolymer and 5-10% epoxy resin;

[0042] The toughening agent comprises 10-15% polyether polyol and 3-5% hydroxyl-terminated polybutadiene;

[0043] The curing agent comprises 8-11% of diphenylmethane diisocyanate and 1-2% of an amine curing agent.

[0044] In this preferred embodiment, the preparation method of the epoxy block copolymer is:

[0045] Select diglycidyl ether and polyoxypropylene glycol,

[0046] Add carboxyl or amino initiator, control the temperature to 50-60°C, initiate polymerization reaction, and form epoxy block copolymer;

[0047] During the copolymerization process, a linear or branched epoxy block copolymer structure is formed by regulating the concentration of the initiator and the reaction time;

[0048] After polymerization, a small amount of thiol compounds and a modifier amine curing agent are added to react at 80° C. for 2 hours to cure to form an epoxy block copolymer with self-healing function.

[0049] In this preferred embodiment, the preparation method of the temperature-responsive microcapsules is:

[0050] Dispersing the lubricant in the water phase, adding polyethylene glycol stearate, and stirring at 50°C to form an emulsion;

[0051] Select polymethyl methacrylate as the shell material of the microcapsule, add it dropwise into the emulsion, and control the pH value at 7-8;

[0052] Poly (N-isopropylacrylamide) was added to the microcapsule preparation, and the microcapsule shell material was maintained at 40-50°C for 30 minutes to undergo structural changes;

[0053] After the coating is completed, the microcapsules are heated to 60°C for curing and then dried under vacuum conditions to form temperature-responsive microcapsules.

[0054] On the other hand, the present invention also provides a method for preparing a sealant for a hyperbaric oxygen chamber, comprising the following steps:

[0055] Mixing the matrix resin: Heat the polyurethane prepolymer to 70-80°C, add the epoxy resin and stir for 30 minutes to fully mix to form the matrix resin;

[0056] Add other materials, such as toughening agent, self-healing material, filler, additive, curing agent and catalyst in sequence;

[0057] Cross-linking and curing: cross-linking and curing layer by layer in the mold;

[0058] Degassing treatment: Place the mixture in a vacuum degassing device and maintain vacuum for 20 minutes to remove bubbles and form a sealant.

[0059] In this preferred embodiment, the layer-by-layer cross-linking and curing includes: pre-curing at 50-60°C for 1 hour, gradually heating up to 80°C, and finally curing at 90°C.

[0060] In this preferred embodiment, the toughening agent is added when the base resin is cooled to 60° C., and stirring is continued for 20 minutes.

[0061] In this preferred embodiment, the filler is subjected to ultrasonic dispersion treatment after being added, and the ultrasonic dispersion treatment time is 20 minutes.

[0062] In this preferred embodiment, the auxiliary agent is added at 70° C. and stirred for 30 minutes. After the curing agent is added, the temperature needs to be maintained at 60° C. and stirred for 30 minutes.

[0063] The following is an experimental result to illustrate the beneficial effects of the sealant proposed by the present invention:

[0064] 1. Sealing test

[0065] Test method: Apply the sealant sample to the simulated high pressure chamber interface and conduct leakage test under different pressure conditions (0.5MPa, 1.0MPa and 1.5MPa). The sealing performance is evaluated by measuring the gas leakage rate.

[0066] Experimental data:

[0067] 0.5MPa: leakage rate ≤0.02mL / min;

[0068] 1.0MPa: leakage rate ≤0.04mL / min;

[0069] 1.5MPa: leakage rate ≤0.06mL / min;

[0070] It can be seen that under high pressure conditions, the leakage rate of the sealant is much lower than the national standard value, proving that it can effectively prevent gas leakage under different pressures and shows excellent sealing and pressure resistance.

[0071] 2. Self-healing performance test

[0072] Test method: Make a tiny cut (1mm) on the sealant surface, place it at room temperature for 24 hours, and then observe the repair of the damaged area; and perform a tensile test to determine the strength recovery rate after self-healing.

[0073] Experimental data:

[0074] Tensile strength before self-healing: 1.5MPa;

[0075] Tensile strength after self-healing: 1.4MPa (recovery rate about 93%);

[0076] It can be seen that the sealant can achieve efficient self-healing at room temperature, and the tensile strength recovery rate reaches 93%, proving that its self-healing material can quickly repair minor damage and greatly extend the service life of the material.

[0077] 3. Temperature responsiveness test

[0078] Test method: Dynamic shear modulus tests were performed on sealant samples of temperature-responsive microcapsules at different temperatures (25°C, 40°C and 60°C) to observe the performance stability of the material under temperature changes.

[0079] Experimental data:

[0080] 25℃: dynamic shear modulus = 120MPa;

[0081] 40℃: dynamic shear modulus = 110MPa;

[0082] 60℃: dynamic shear modulus = 105MPa;

[0083] It can be seen that under high temperature conditions, the dynamic shear modulus of the sealant only decreases slightly, proving that the microcapsules can release lubricants as the temperature changes to adjust the flexibility and strength of the colloid, thereby maintaining stable sealing performance under different temperature conditions.

[0084] In summary, the sealant of the present invention not only improves the sealing of the material, but also significantly enhances the durability by adopting a composite matrix resin structure of polyurethane prepolymer and epoxy resin, so that the sealant maintains excellent performance under high pressure and high temperature environments. The composite matrix can effectively resist the erosion of pressure and oxygen on the material and extend the service life of the sealant. The epoxy block copolymer and temperature-responsive microcapsules with self-healing properties are used to give the sealant self-healing ability under high pressure environments. The linear and branched structures in the epoxy block copolymer are precisely controlled so that the sealant can quickly self-heal when damaged, repair tiny cracks and surface damage, and significantly improve the long-term sealing performance of the sealant. The temperature-responsive microcapsules in the present invention can release internal lubricants under specific temperature conditions, so that the flexibility and strength of the sealant can be automatically adjusted in temperature changes. This design enables the sealant to maintain stable sealing performance under temperature fluctuations or extreme temperature conditions, thereby adapting to sealing requirements in different environments. The sealant has high flexibility and strength while ensuring sealing performance by adding toughening agents (polyether polyol and terminal hydroxyl polybutadiene) and fillers (nano silicon dioxide, boron carbide powder, etc.) to the matrix, meeting the stringent requirements of the hyperbaric oxygen chamber for sealing materials. The introduction of nanofillers and reinforcing additives improves the mechanical properties of the colloid, so that the sealant has stronger impact resistance when under pressure or vibration. By introducing ultraviolet absorbers and nano cerium oxide (CeO2), the sealant has stronger ultraviolet resistance and anti-aging properties. Even under long-term lighting conditions, the material can effectively delay the aging process and maintain a high-performance sealing effect, thereby significantly improving the application life and reliability of the sealant. The preparation method of the present invention achieves uniform distribution of each component in the sealant through fine control of the steps of staged cross-linking curing, ultrasonic dispersion treatment and degassing, thereby improving the structural stability and overall performance of the sealant. The temperature control and ultrasonic dispersion technology of the layer-by-layer curing process fully combine components such as fillers and toughening agents, further optimizing the sealing, strength and durability of the sealant.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A sealant for a hyperbaric oxygen chamber, characterized in that: include: Matrix resin 50%-60%, toughening agent 13%-17%, curing agent 9%-13%, self-healing material 5%-9%, other materials 10%-20%; The self-healing material comprises 3%-5% of epoxy block copolymer and 2%-4% of temperature responsive microcapsules.

2. A sealant for a hyperbaric oxygen chamber according to claim 1, characterized in that: The other materials include fillers, additives and catalysts; The filler comprises 2-5% nano silicon dioxide, 1-3% boron carbide powder, 1-2% carbon nanotubes and 2-3% graphene-alumina composite nano powder; The auxiliary agent includes 2.5-4% phthalic acid esters, 1-2% nano cerium oxide CeO2, and 0.5-1% ultraviolet absorber; The catalyst comprises 0.1-0.3% of an organic tin compound and 0.1-0.2% of an organic silane coupling agent.

3. The sealant for a hyperbaric oxygen chamber according to claim 1, characterized in that: The matrix resin includes 45-50% polyurethane prepolymer and 5-10% epoxy resin; The toughening agent comprises 10-15% polyether polyol and 3-5% hydroxyl-terminated polybutadiene; The curing agent comprises 8-11% of diphenylmethane diisocyanate and 1-2% of an amine curing agent.

4. The sealant for a hyperbaric oxygen chamber according to claim 1, characterized in that: The preparation method of the epoxy block copolymer is: Select diglycidyl ether and polyoxypropylene glycol, Add carboxyl or amino initiator, control the temperature to 50-60°C, initiate polymerization reaction, and form epoxy block copolymer; During the copolymerization process, a linear or branched epoxy block copolymer structure is formed by regulating the concentration of the initiator and the reaction time; After polymerization, a small amount of thiol compounds and a modifier amine curing agent are added to react at 80° C. for 2 hours to cure to form an epoxy block copolymer with self-healing function.

5. The sealant for a hyperbaric oxygen chamber according to claim 1, characterized in that: The preparation method of the temperature-responsive microcapsules is as follows: Dispersing the lubricant in the water phase, adding polyethylene glycol stearate, and stirring at 50°C to form an emulsion; Select polymethyl methacrylate as the shell material of the microcapsule, add it dropwise into the emulsion, and control the pH value at 7-8; Poly (N-isopropylacrylamide) was added to the microcapsule preparation, and the microcapsule shell material was maintained at 40-50°C for 30 minutes to undergo structural changes; After the coating is completed, the microcapsules are heated to 60°C for curing and then dried under vacuum conditions to form temperature-responsive microcapsules.

6. A method for preparing a sealant for a hyperbaric oxygen chamber according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing the matrix resin: Heat the polyurethane prepolymer to 70-80°C, add the epoxy resin and stir for 30 minutes to fully mix to form the matrix resin; Add other materials, such as toughening agent, self-healing material, filler, additive, curing agent and catalyst in sequence; Cross-linking and curing: cross-linking and curing layer by layer in the mold; Degassing treatment: Place the mixture in a vacuum degassing device and maintain vacuum for 20 minutes to remove bubbles and form a sealant.

7. The method for preparing a sealant for a hyperbaric oxygen chamber according to claim 6, characterized in that: The layer-by-layer cross-linking and curing includes: pre-curing at 50-60° C. for 1 hour, gradually heating up to 80° C., and finally curing at 90° C.

8. The method for preparing a sealant for a hyperbaric oxygen chamber according to claim 6, characterized in that: The toughening agent was added when the base resin was cooled to 60° C. and stirred for 20 minutes.

9. The method for preparing a sealant for a hyperbaric oxygen chamber according to claim 6, characterized in that: After the filler is added, ultrasonic dispersion treatment is performed, and the ultrasonic dispersion treatment time is 20 minutes.

10. The method for preparing a sealant for a hyperbaric oxygen chamber according to claim 6, characterized in that: The auxiliary agent is added at 70° C. and stirred for 30 minutes. After the curing agent is added, the temperature needs to be maintained at 60° C. and stirred for 30 minutes.

Citation Information

Patent Citations

  • Method for producing energy-saving scagliola containing microencapsulated phase change materials

    CN101633197A

  • Method for preparing epoxy resin composite material with self-healing function

    CN102993640A

  • One-step synthesis method for polyurethane material with gradually-changing modulus

    CN104961877A

  • Preparation method of polyacrylate-polyester I-polyester II triblock copolymer

    CN110746586A

  • Preparation method of polyurethane composite microcapsule and application of polyurethane composite microcapsule in self-repairing of epoxy resin

    CN118290903A